Looking Back 30 Years: AIDS, San Francisco, and How We Learned There and Then - Jon Wrigglesworth (Adult Education Research Conference, 2014)
Employing Cultural Historical Activity Theory as a theoretical lens, this study examines the first three years of the AIDS crisis, with the purpose of examining how the San Francisco gay community (SFGC) and the San Francisco medical community (SFMC) entered a cycle of expansive learning while confronting the AIDS crisis.